The effect on price, liquidity and risk when stocks are added to and deleted from a sustainability index: Evidence from the Asia Pacific context - Cheung, Adrian; Roca, E. (Elsevier BV * North-Holland, 2013)
We examine the impact on returns, risk and liquidity of stocks in the Asia Pacific markets when included into and deleted from the Dow Jones Sustainability World Index over the period 2002–2010. Using an event study methodology, we test five existing hypotheses and two new ones, called the ‘‘sustainability taste hypothesis’’ and ‘‘sustainability redundancy hypothesis’’, which we developed. Consistent with the ‘‘sustainability redundancy hypothesis’’, we find that both index addition and index deletion stocks experience a significant decline in returns, an increase in trading volume, no change in systematic risk and an increase in idiosyncratic risk. This indicates that sustainability matters to Asia Pacific investors, although in a somewhat negative manner.